Water Quality Study for Grouper Mariculture in Divur Bay Dullah Island, Tual City - Daniel Djokosetiyanto; Henny Fitri Nawati; Machfud Machfud; Achmad Fahrudin (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Water quality is one of the factors that determine the feasibility and success of the development of grouper mariculture. The objective of this research was to analyze water quality which was prepared for grouper mariculture. This research was carried out in Divur Bay, Dullah island of Tual City. The water quality parameters observed were including temperature, brightness, salinity, pH, current velocity, depth, substrate type, DO, nitrate and phosphate in ten stations spread in Divur Bay. Water quality data were analyzed descriptively. The results showed that Divur Bay was feasible for the grouper culture development with a range of values of temperature, brightness, salinity, pH, current velocity, depth, DO, nitrate and phosphate obtained were 30-31oC; 2.28-7.86 m; 33-35 ppt; 7.7-8.1; 0.06-0.617m/s; 2..28-18.58 m; 3.7-4.8 ppm; 0.0015-0.219 ppm; 0.0076-0.0767 ppm.